Field monitoring of sprinting power-force-velocity profile before, during and after hamstring injury: two case reports - Mendiguchia, J.; Edouard, P.; Samozino, P.; Brughelli, M.; Cross, M.; Ross, A.; Gill, N.; Morin, J.-B. (Journal of Sports Sciences, 2016)
Very little is currently known about the effects of acute hamstring injury on over-ground sprinting mechanics. The aim of this research was to describe changes in power-force-velocity properties of sprinting in two injury case studies related to hamstring strain management: Case 1: during a repeated sprint task (10 sprints of 40 m) when an injury occurred (5th sprint) in a professional rugby player; and Case 2: prior to (8 days) and after (33 days) an acute hamstring injury in a professional soccer player. A sports radar system was used to measure instantaneous velocity-time data, from which individual mechanical profiles were derived using a recently validated method based on a macroscopic biomechanical model. Variables of interest included: maximum theoretical velocity (V0) and horizontal force (FH0), slope of the force-velocity (F-v) relationship, maximal power, and split times over 5 and 20 m. For Case 1, during the injury sprint (sprint 5), there was a clear change in the F-v profile with a 14% greater value of FH0 (7.6-8.7 N/kg) and a 6% decrease in V0 (10.1 to 9.5 m/s). For Case 2, at return to sport, the F-v profile clearly changed with a 20.5% lower value of FH0 (8.3 vs. 6.6 N/kg) and no change in V0. The results suggest that the capability to produce horizontal force at low speed (FH0) (i.e. first metres of the acceleration phase) is altered both before and after return to sport from a hamstring injury in these two elite athletes with little or no change of maximal velocity capabilities (V0), as evidenced in on-field conditions. Practitioners should consider regularly monitoring horizontal force production during sprint running both from a performance and injury prevention perspective.